Controlling the π‐Stacking Behavior of Pyrene Derivatives: Influence of H‐Bonding and Steric Effects in Different States of Aggregation. Issue 9 (25th April 2013) - Haedler, Andreas T.; Misslitz, Holger; Buehlmeyer, Christian; Albuquerque, Rodrigo Q.; Köhler, Anna; Schmidt, Hans‐Werner
Abstract The performance of opto‐electronic devices built from low‐molecular‐weight dye molecules depends crucially on the stacking properties and the resulting coupling of the chromophoric systems. Herein we investigate the influence of H‐bonding amide and bulky substituents on the π‐stacking of pyrene‐containing small molecules in dilute solution, as supramolecular aggregates, and in the solid state. A set of four pyrene derivatives was synthesized in which benzene or 4‐tert‐butyl benzene was linked to the pyrene unit either through an ester or an amide. All four molecules form supramolecular H‐aggregates in THF solution at concentrations above 1×10−4 mol L−1. These aggregates were transferred on a solid support and crystallized. We investigate: the excimer formation rates within supramolecular aggregates; the formation of H‐bonds as well as the optical changes during the transition from the amorphous to the crystalline state; and the excimer to monomer fluorescence ratio in crystalline films at low temperatures. We reveal that in solution supramolecular aggregation depends predominantly on the pyrene chromophores. In the crystalline state, however, the pyrene stacking can be controlled gradually by H‐bonding and steric effects. These results are further confirmed by molecular modeling. This work bears fundamental information for tailoring the solid state of functional optoelectronic materials.